Systematic observation of participatory interaction in university lectures: a multiple case study with a mixed methods approach - Tronchoni, Héctor; Izquierdo, Conrad; Anguera, M. Teresa (Frontiers in Psychology, 2024)
Introduction In order to improve and innovate the face-to-face instructional task in postgraduate and doctoral university teaching encompasses different formats of participatory interaction (PI), considered to be social medium facilitators of deep learning, including the development of autonomous expert activity. The purpose of this article is to establish the use of systematic observation and lag sequential analysis as a conceptual-methodological choice to base the review of social-constructivist instructional practice that is taught in an expository format prepared by the teacher. Method The systematic observation of the expert’s expository session from its inception to its conclusion was approached from a mixed methods perspective as a subject of multiple case studies. A total of four postgraduate teachers were selected. A purpose-built observational instrument was constructed. The data quality was evaluated with intra-observer agreement tests by calculating Cohen’s kappa coefficient (k). After the data matrices for each case were obtained, all possible file aggregations of the data were performed to detect the existence of common structures in the patterns through lag sequential analysis. Results The sequential patterns of replicated and common lags of the multiple cases describe the chaining of the observed events, which characterizes the participatory interaction. Twelve lag sequential patterns have been identified that function as dialogical links, generated by the probability that the category “question” is linked to the conditioned events of “speech direction” and “exchange orientation.” Discussion Having constructed a theoretical interpretative scheme of the replicated patterns, we discuss the results. First, the significant results of the lag sequential analysis as examples of basic patterns extracted from their way of conducting expert expository sessions. As such, they can be reviewed with the formative purpose of reflecting on their potential for change when they are understood as dialogical links of participatory interaction committed to deep learning and the development of expert autonomy. Second, there is a training step consisting of the use of self-observation and the observation that teachers can make of the expert expository task. Finally, we conclude that non-intrusive systematic observation is a good choice when channeling the gradual and renewed improvement of participatory interaction with an expert expository format (§EF) and a mixed methods methodology.